Religious Moderation in Primary Education: Experiences of Teachers in Indonesia and Malaysia - Muslih; Muslam; Ramiaida Darmi; Siti Rosilawati Ramlan; Rizal Rahman Abdullah; M. Aqil Luthfan (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose - This article discusses how Islamic religious education teachers in primary schools in Indonesia and Malaysia have understood and disseminated the concept of religious moderation to students in the classroom. Design/methods/approach – This research uses field research, which uses a descriptive qualitative approach. The research data was obtained qualitatively from in-depth interviews and observations. Findings – The findings show that most of the teachers who took part in this study have a good knowledge of religious moderation. They also show that the teachers internalized religious moderation for students in different ways according to the conditions of their respective schools. The findings also show that the teachers find shortcomings in delivering moderation messages to students. The significance of this study lies in its theoretical contribution, which confirms that schools are open places for the development of any ideology, including radicalism. Research implications/limitations – This study recommends that the state prevent radicalism by mainstreaming the ideology of moderation, including training to improve teachers' knowledge of religious moderation and effective ways to instil religious moderation in students. Originality/value – This research contributes to our understanding of the need for teachers to introduce religious moderation in basic education. Moderate behaviour in religion needs to be instilled in students from an early age to prevent them from being exposed to radicalism that has begun to penetrate the realm of education.